Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.4317/jced.59974
|View full text |Cite
|
Sign up to set email alerts
|

Application of the London Atlas Software App 2nd edition for the radiographic assessment of dental development

Abstract: Background Assessing the dental development of children and adolescents is an important part of treatment planning. The radiographic visualization of dental developmental stages prior to age estimation is currently feasible by means of digital software apps. Testing the existing software tools is necessary to safeguard application in practice. This study applied the London Atlas Software App 2nd edition™ for dental age estimation in Brazilian children. Material and Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 21 publications
(30 reference statements)
0
6
1
Order By: Relevance
“…Contrasting, when The London Atlas was applied based on the developing permanent dentition of Brazilian individuals aged 6-15.99 years ( 7 ), the MAE was only 0.56 and 0.60 years The current results, based solely on third molar formation in the age group 16-22.99 years, showed MAE of 1.76 and 1.52 years for females and males, respectively. These outcomes seem to point out to a potentially acceptable performance of the method since third molar age estimation often leads to MAE rates that could reach over 2.0 years ( 20 , 21 ).…”
Section: Discussioncontrasting
confidence: 85%
See 4 more Smart Citations
“…Contrasting, when The London Atlas was applied based on the developing permanent dentition of Brazilian individuals aged 6-15.99 years ( 7 ), the MAE was only 0.56 and 0.60 years The current results, based solely on third molar formation in the age group 16-22.99 years, showed MAE of 1.76 and 1.52 years for females and males, respectively. These outcomes seem to point out to a potentially acceptable performance of the method since third molar age estimation often leads to MAE rates that could reach over 2.0 years ( 20 , 21 ).…”
Section: Discussioncontrasting
confidence: 85%
“…Out of 2.527 entries detected with a dedicated search string, the London Atlas has not been included amongst the top ranked methods ( 14 ). Regarding the performance of the method, previous studies have found an overall accuracy of 79.9% ( 15 ), while others have demonstrated concern especially when the method is applied solely based on third molars ( 7 , 16 ). Most of the performance tests that have been accomplished with the London Atlas have followed the common methodological structure of dental age estimation studies and quantified the difference between chronological and estimated ages ( 7 , 16 ).…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations